Factors Affecting Tax Revenue Collection Through the TaxRIS System in Luang Prabang Province - Sisavath, Lingo; Siphanthong, Bounthavy; Sioudomphan, Soutthavone (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This research aims to: 1) Study the efficiency of tax revenue collection through the TaxRIS system in LuangPrabang city and 2) Factors affecting tax revenue collection through the TaxRIS system in LuangPrabang province. Using time series data to analyze the parameters of the linear regression equation using the least squares method and time series model using SPSS version 27. The research results found that tax revenue through the TaxRIS system from 2023 to 2025 has changed irregularly with increases and decreases each quarter each year. From the implementation results of tax revenue collection through the TaxRIS system in LuangPrabang city compared to the specified implementation plan, it is seen that the ratio between the implementation results and the plan is less than 1 in every quarter and every year; in general, tax revenue collection in LuangPrabang cityhas not been achieved according to the specified plan, resulting in tax revenue collection in LuangPrabang citynot being effective. As for the results of the correlation test of factors affecting tax revenue collection through the TaxRIS system in LuangPrabang city, it was found that the number of enterprises that paid taxes through the TaxRIS system and the inflation rate factor were related in the same direction and resulted in an increase in tax revenue. As for the budget factor in tax collection, it was related in the opposite direction and resulted in a decrease in tax revenue with a statistical significance level 0.05. Through the forecasting of tax revenue, it was found that tax revenue changed in an irregular manner, some months increasing and some months decreasing, which was due to changes in the income of enterprises operating in LuangPrabang city, including changes in the number of enterprises that paid taxes through the TaxRIS system itself.